Cognitive measures lacking in EHR prior to dementia or Alzheimer's disease diagnosis. Issue 7 (3rd March 2021) - Maserejian, Nancy; Krzywy, Henry; Eaton, Susan; Galvin, James E.
Abstract: Introduction: The extent that cognitive measures are documented in electronic health records (EHR) is important for quality care and addressing disparities in timely diagnosis of dementia or Alzheimer's disease (AD). Methods: Analysis of U.S. EHR data to describe the frequency and factors associated with cognitive measures prior to diagnosis of dementia (N = 111, 125) or AD (N = 30, 203). Results: Only 11% of dementia patients and 24% of AD patients had a cognitive measure documented in the 5 years prior to diagnosis. Black race, older age, non‐commercial health insurance, lower mean neighborhood income, greater in‐patient stays, and fewer out‐patient visits were associated with lacking cognitive measures. Discussion: Extensive missing cognitive data and differences in the availability of cognitive measures by race, age, and socioeconomic factors hinder patient care and limit utility of EHR for dementia research. Structured fields and prompts for cognitive data inputs at the point of care may help address these gaps.